Personal Determination of Self-Confidence in Youth - Nataliia Shevchenko; Oksana Kuzmych; Oleksandra Hmyrina (Insight: the psychological dimensions of society, 2024)
The aim of the study is to determine the peculiarities of self-confidence development and its personal determinants in youth. Methods. Theoretical: analysis, comparison, systematization, generalization of scientific literary sources and experimental research data; empirical: psychodiagnostic methods: “Assessment of self-confidence” (Zelinska, 2010); “Self-assessment test-questionnaire” (Kolesnichenko et al.,, 2020); “Method of research on self-evaluation of the individual” (Perih, 2017); “Motivation for success and failure avoidance” (Kolesnichenko et al., 2020); “Locus of Control” (Kolesnichenko et al., 2020); “General self-efficacy test” (Kokun et al., 2021); mathematical and statistical methods. Results. The results of an empirical research of the development of self-confidence in youth were presented. The research of the development of the cognitive component of self-confidence showed that the respondents were aimed at self-awareness, obtaining information about themselves, they were inclined to study their inner world, and analyze personal potential. The research of the emotional and value component proved the favorable attitude of young people towards themselves, but dissatisfaction with certain personal qualities and behavior patterns. As a result of the research of the behavioral component, it was found that the level of self-respect of young men of both age groups corresponds to the average level: they were characterized by a critical attitude towards themselves, they strive for the development of their own “Self”. The personal determinants of self-confidence in youth were researched. The research of dignity manifestation proved that the indicators of young people exceed the average level, they have dignity. The results of the research of self-esteem showed that the subjects were characterized by a vague and undifferentiated perception of their ideal and real qualities. The research of the internality of subjective control demonstrated that, depending on the situation, it was a characteristic of the majority of the respondents to attribute responsibility for life events both to their own efforts and to external factors. The research of the motivational tendency of young men made it possible to state that the motivational pole of the respondents was not clearly expressed. The results of the self-efficacy research proved contextuality of young people’s belief in the effectiveness of their actions. Discussion and сonclusions. The assumption that self-confidence in youth was meaningfully determined by age-related new formations and influenced by personal determinants (dignity; adequate self-esteem; internality of subjective control; motivation for success; belief in one’s own self-efficacy) was confirmed.